PEACEKEEPING AND SECURITY MECHANISMS FOR REGULATING CONTEMPORARY INTERNATIONAL RELATIONS - Іnna Vivchar; Roman Kret; Oksana Kundeus (Вісник Харківського національного університету імені В. Н. Каразіна: Серія "Питання політології")
The article explores multilateral institutions and their approaches to stabilizing and resolving conflicts on a global scale. In particular, the author analyzes the key international organizations, such as the United Nations, the Organization for Security and Co-operationin Europe, the North Atlantic Treaty Organization, and the European Union, highlighting their roles in ensuring international security and maintaining peace. The research shows that the UN serves as a central actor in global peacekeeping activities, conducting peacekeeping missions in conflict regions and working on conflict prevention through diplomacy and sanctions. Its Security Councilis a key decision-making body in addressing international security challenges. The OSCE, as the largest regional organization, focuses on conflict resolution in Europe and Central Asia, utilizing preventive diplomacy, election monitoring, and observation missions. NATO, as a defense alliance, directs its efforts toward collective security and stabilization through peacekeeping missions and operations in crisis regions, particularly in the context of hybrid threats. The EU, in turn, develops its own security mechanisms through the Common Foreign and Security Policy, aimed at protecting Europe’s interests and promoting global peace. The article examines the interaction of these organizations in contemporary international relations and their effectiveness in responding to new challenges such as terrorism, cyber threats, and climate change. The author also provides practical recommendations for improving peacekeeping and security mechanisms to more effectively address modern challenges to international stability and ensure lasting peace.